2012
DOI: 10.1021/bm300193f
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillation Mechanism of a Model Intrinsically Disordered Protein Revealed by 2D Correlation Deep UV Resonance Raman Spectroscopy

Abstract: Understanding of numerous biological functions of intrinsically disordered proteins (IDPs) is of significant interest to modern life science research. A large variety of serious debilitating diseases are associated with the malfunction of IDPs including neurodegenerative disorders and systemic amyloidosis. Here we report on the molecular mechanism of amyloid fibrillation of a model IDP (YE8) using 2D correlation deep UV resonance Raman spectroscopy. YE8 is a genetically engineered polypeptide, which is complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 74 publications
2
20
0
Order By: Relevance
“…Using two‐dimensional Correlation DUVRR, we previously applied a two‐component model approach to describe the high level of complexity of fibrillation events in the transition of unordered YE8 to an amyloid‐like β‐sheet structure . In this fibrillation mechanism model, it was revealed that initially unordered YE8 underwent a global structural rearrangement of tyrosine residues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using two‐dimensional Correlation DUVRR, we previously applied a two‐component model approach to describe the high level of complexity of fibrillation events in the transition of unordered YE8 to an amyloid‐like β‐sheet structure . In this fibrillation mechanism model, it was revealed that initially unordered YE8 underwent a global structural rearrangement of tyrosine residues.…”
Section: Resultsmentioning
confidence: 99%
“…The polypeptides were incubated for 45 days, and after this period, as seen from the DUVRR spectra in Figure , 8PD and YE8 folded whereas the less‐pronounced amide I bands of 1PD and 5PD suggested those peptides to be only partially folded. The combined CD spectra of all the polypeptides were subsequently treated and yielded three principal components, with Component 1 (PC1) contributing 16.01% and Components 2 (PC2) and 3 (PC3) contributing 32% and 51.91%, respectively (Figure ). The three principal component models can rationalize the major variance of the data, and overfitting can be avoided.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the fluorescence intensity of DACM‐labeled peptides at 465 nm increases over time (see Figure S13) as folding proceeds as measured by CD (see Figure S5). Though fibrillation of the folded peptides is known to be relatively slow, samples for resonance energy transfer studies were prepared by centrifugation (3220 ×g ) to remove any aggregates formed. The influence of aggregation on DACM fluorescence is difficult to assess, however fibrils were not detectable by ThT fluorescence (Figure S14), showing that fibril concentration was less than 1 μ m .…”
Section: Figurementioning
confidence: 99%
“…15,22 Kupfer et al used a combination of resonance Raman measurements and density functional theory (DFT) calculations to unveil the mechanisms involved in the self-healing of supramolecular polymers. [32][33][34][35][36][37][38] Sinzawa et al for example studied the pre-melting behaviour of polyethylene between 30 and 100 °C with 2D correlation Raman spectroscopy. 2 Harrington et al applied strain-dependent Raman spectroscopy to investigate reversible protein backbone conformation changes in whelk egg capsules of Busycotypus canaliculatus.…”
Section: Introductionmentioning
confidence: 99%